Antibiotic susceptibility of Escherichia coli isolated from neonates admitted to neonatal intensive care units across China from 2015 to 2020 - Xiao, Ruiqi; Li, Ying; Liu, Xiaowei; Ding, Yijun; Lai, Jidong; Li, Yangfang; Kang, Wenqing; Zou, Peicen; Wang, Jie; Du, Yue; Zhang, Jinjing; Wang, Yajuan (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Escherichia coli is one of the most common pathogens causing neonatal infections. Recently, the incidence and drug resistance of E. coli have increased, posing a major threat to neonatal health. The aim of this study was to describe and analyze the antibiotic resistance and multilocus sequence typing (MLST) characteristics of E. coli derived from infants admitted to neonatal intensive care units (NICUs) across China. Methods: In this study, 370 strains of E. coli from neonates were collected. E. coli isolated from these specimens were subjected to antimicrobial susceptibility testing (by broth microdilution method) and MLST. Results: The overall resistance rate was 82.68%, with the highest rate of methicillin/sulfamethoxazole (55.68%) followed by cefotaxime (46.22%). Multiple resistance rate was 36.74%, 132 strains (35.68%) had extended-spectrum β-lactamase (ESBL) phenotype and 5 strains (1.35%) had insensitivity to the tested carbapenem antibiotics. The resistance of E. coli isolated from different pathogenicity and different sites of infections varied, strains derived from sputum were significantly more resistant to β-lactams and tetracyclines. Currently, the prevalence spectrum in NICUs was dominated by ST1193, ST95, ST73, ST69 and ST131 across China. And the multidrug resistance of ST410 was the most severe. ST410 had the highest resistance rate to cefotaxime (86.67%), and its most common multidrug resistance pattern was β-lactams + aminoglycosides + quinolones + tetracyclines + sulfonamides. Conclusions: Substantial proportions of neonatal E. coli isolates were severely resistant to commonly administered antibiotics. MLST results can suggest the prevalent characteristics of antibiotic resistance in E. coli with different ST types.